2011
DOI: 10.1080/10401334.2011.586917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peyton's Four-Step Approach on Objective Performance Measures in Technical Skills Training: A Controlled Trial

Abstract: Peyton's Four-Step Approach is superior to standard instruction with respect to professionalism and accompanying doctor-patient communication and leads to faster performance when trainees perform the learned skill for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 29 publications
10
109
2
6
Order By: Relevance
“…Die Nutzung stichsicherer Instrumente muss intensiv eingeübt werden. Die positive Wirkung geeigneter "Skills Labs" und der Einführung geeigneter stichsicherer Instrumente ist in Studien gut belegt [25][26][27][28][29] Es zeigt sich des Weiteren, dass die flächendeckende Einführung stichsicherer Instrumente noch nicht vollzogen wurde. Zwar hatte das Universitätsklinikum Düsseldorf vollständig auf stichsichere Instrumente umgestellt, aber ganz offensichtlich nicht alle weiteren Bereiche, in denen die Studierenden tätig sind.…”
Section: Abstract ▼unclassified
“…Die Nutzung stichsicherer Instrumente muss intensiv eingeübt werden. Die positive Wirkung geeigneter "Skills Labs" und der Einführung geeigneter stichsicherer Instrumente ist in Studien gut belegt [25][26][27][28][29] Es zeigt sich des Weiteren, dass die flächendeckende Einführung stichsicherer Instrumente noch nicht vollzogen wurde. Zwar hatte das Universitätsklinikum Düsseldorf vollständig auf stichsichere Instrumente umgestellt, aber ganz offensichtlich nicht alle weiteren Bereiche, in denen die Studierenden tätig sind.…”
Section: Abstract ▼unclassified
“…The approach would nonetheless be interesting regarding wider education (medical laypersons). Krautter et al 2011 [14] also illustrated the superiority of Peyton’s approach on another level in terms of the instruction of gastric-tube insertion: Procedurally compared (through checklists, 13 dichotomous items) the 4-Step method was not superior to the classic instruction method, it did however display advantages with respect to doctor-patient communication, professional manner and the speed of execution of the activity. This aspect was also shown by Lund et al [15] for the instruction of an IV cannulation, although the intervention group (4-Step method) in this study was also superior to the control group (“See one, do one”) in procedural comparison (25 dichotomous items).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the surveys conveyed that students taught with the help of this method profited from their instruction in comparison with other groups [11], [12], [14], [15], [16]. Other surveys found no advantages to the Peyton method [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rodney Peyton's four step technique involves demonstration, deconstruction, comprehension and performance. 4,5 Evaluation was done with Kirkpatrik model using a specially designed Objective Structured Clinical Examination forms and scoring sheets (Table 1) The study intended to train and assess the clinical skills of the trainees. After going through the OSCE (Objective Structured Clinical Evaluation) pre and post test scores it can be observed that the overall skills of the subjects improved.…”
Section: Methodsmentioning
confidence: 99%